2017
DOI: 10.3390/bs7030052
|View full text |Cite
|
Sign up to set email alerts
|

FITNET’s Internet-Based Cognitive Behavioural Therapy Is Ineffective and May Impede Natural Recovery in Adolescents with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome. A Review

Abstract: The Dutch Fatigue In Teenagers on the interNET (FITNET) study claimed that after 6 months, internet based cognitive behaviour therapy in adolescents with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), led to a 63% recovery rate compared to 8% after usual care, and that this was maintained at long term follow up (LTFU). Our reanalysis shows that their post-hoc definition of recovery included the severely ill, the unblinded trial had no adequate control group and it used lax selection criteria as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…'Indeed, it is difficult to imagine how such a large-scale investigation could have developed, proceeded and passed through the review process unless its scientific failings were actually characteristic of its field'. Analysis of the Dutch FITNET trial of Internet CBT for adolescents (Ghatineh and Vink, 2017), of the Dutch FatiGo trial of multidisciplinary rehabilitation treatment (Vink and Vink-Niese, 2018a) and of five Dutch hallmark CBT studies (Twisk and Corsius, 2017) supported this observation. A recent re-analysis of the Cochrane exercise review for CFS (Vink and Vink-Niese, 2018b) revealed a number of methodological concerns with many of the studies reviewed as part of the Cochrane review of GET for CFS and a lack of objective evidence for improvement in physical function.…”
Section: Introductionmentioning
confidence: 87%
“…'Indeed, it is difficult to imagine how such a large-scale investigation could have developed, proceeded and passed through the review process unless its scientific failings were actually characteristic of its field'. Analysis of the Dutch FITNET trial of Internet CBT for adolescents (Ghatineh and Vink, 2017), of the Dutch FatiGo trial of multidisciplinary rehabilitation treatment (Vink and Vink-Niese, 2018a) and of five Dutch hallmark CBT studies (Twisk and Corsius, 2017) supported this observation. A recent re-analysis of the Cochrane exercise review for CFS (Vink and Vink-Niese, 2018b) revealed a number of methodological concerns with many of the studies reviewed as part of the Cochrane review of GET for CFS and a lack of objective evidence for improvement in physical function.…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, another problem with outcomes assessed via questionnaires in a non-blinded trial is “response-shift bias”. This occurs when an intervention leads individuals to change their evaluation standard regarding the dimension measured, leading the therapist (and, often, also the patient) to conclude erroneously that the treatment has worked [ 29 , 33 ]. This form of bias is even more of a problem in CBT trials for ME/CFS, because this specific form of CBT aims to modify participants’ beliefs and perceptions of their symptoms [ 34 ].…”
Section: Analysis Of the Evidence Relied Upon By The Iqwig Reportmentioning
confidence: 99%
“…This data is taken from a pediatric CBT trial of FITNET in the Netherlands (41). The Dutch trial has been criticized for over-stating benefits via post-hoc selection of recovery measures and for including young patients with general fatigue issues (42). Interestingly, at long-term follow up in the Dutch FITNET study (2 years+), recovery stood at 64% for CBT-GET participants, but 52.8% for usual care participants (43).…”
Section: Implications For Treatmentmentioning
confidence: 99%